2014
DOI: 10.1155/2014/608053
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and Antioxidant Activity of Bread Enriched with Broccoli Sprouts

Abstract: This study is focused on antioxidant and anticancer capacity of bread enriched with broccoli sprouts (BS) in the light of their potential bioaccessibility and bioavailability. Generally, bread supplementation elevated antioxidant potential of product (both nonenzymatic and enzymatic antioxidant capacities); however, the increase was not correlated with the percent of BS. A replacement up to 2% of BS gives satisfactory overall consumers acceptability and desirable elevation of antioxidant potential. High activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 45 publications
4
57
1
3
Order By: Relevance
“…Incorporation of powdered broccoli stalks also resulted in lower a* values when compared to the control ( p < 0.05). Similar results were obtained by Gawlik‐Dziki et al () who reported that wheat breads containing broccoli sprouts at concentrations ranging from 1% to 5% (w/w) were greener when compared to the control.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Incorporation of powdered broccoli stalks also resulted in lower a* values when compared to the control ( p < 0.05). Similar results were obtained by Gawlik‐Dziki et al () who reported that wheat breads containing broccoli sprouts at concentrations ranging from 1% to 5% (w/w) were greener when compared to the control.…”
Section: Resultssupporting
confidence: 89%
“…In addition, addition of broccoli leaves into gluten‐free mini sponge cakes significantly increased their antioxidant capacity previously (Drabińska, Ciska, Szmatowicz, & Krupa‐Kozak, ). Gawlik‐Dziki et al () also obtained increased antioxidant capacity after inclusion of broccoli sprouts into wheat bread formulations at concentrations ranging from 1% to 5% (w/w) and similar results were reported by Lee () who obtained DPPH·scavenging activity values ranging from 17.6% to 45.5% after inclusion of broccoli at concentrations ranging from 2.5% to 10.0% (w/w). Although powdered broccoli stems showed a higher antioxidant activity in vitro when compared to powdered broccoli leaves, the antioxidant capacity of the breads containing these co‐products were not significantly different to each other.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The addition of MFP already in the amount of 2.5% resulted in very large changes in the TPC from 0.88 to 2.12 GAE/g dw. Many authors reported that phenolics can form complexion with protein in matrix, and heating process also may alter phenolic antioxidants in bread during baking in different extents [38,39].…”
Section: Antioxidant Propertiesmentioning
confidence: 99%